EVALUASI PROGRAM PENDIDIKAN DAN PELATIHAN MENGGUNAKAN APLIKASI BERBASIS ANDROID DI ARSIP NASIONAL REPUBLIK INDONESIA (ANRI) - Vicihayu Dyah Mulyaningrum; Sumardi .; Eka Suhardi (Universitas Pakuan, 2020)
EVALUATION OF EDUCATION AND TRAINING PROGRAMS USING ANDROID-BASED APPLICATIONS IN THE NATIONAL ARCHIVES OF THE REPUBLIC OF INDONESIAThis study is intended to find out of how to develop Evaluation Development Program for Archival Education and Training Based on Android System. This research was conducted on the Nation Archive of Republic Indonesia. The research method used in this research was R D and the instrument of the study was a questionnaire distributed to participants in archival education and training. The results showed that in developing program following the 3-D model. The 3-D model consists of 3 stages: define, design and develop. In the first stage (defining), it was found that the evaluation carried out was still utilizing paper media. It did not support the implementation of e-Government systems. The second step (design) was started from making the design, and continued with validating the product to the team experts. The third step was development. This last stage was carried out by a small scale of trial which was participated with 47 participants. In the small-scale of trial phase was to detect the shortcomings of the product development and further development products would be fixed and be ready for large-scale trials. The large-scale of trial was attended by 95 participants. The analyzing result of the large scale trial had shown that the development product was valid and ready to be disseminated.